2014
DOI: 10.15283/ijsc.2014.7.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Translational Research: Palatal-derived Ecto-mesenchymal Stem Cells from Human Palate: A New Hope for Alveolar Bone and Cranio-Facial Bone Reconstruction

Abstract: The management of facial defects has rapidly changed in the last decade. Functional and esthetic requirements have steadily increased along with the refinements of surgery. In the case of advanced atrophy or jaw defects, extensive horizontal and vertical bone augmentation is often unavoidable to enable patients to be fitted with implants. Loss of vertical alveolar bone height is the most common cause for a non primary stability of dental implants in adults. At present, there is no ideal therapeutic approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 19 publications
1
25
0
6
Order By: Relevance
“…Its capability for rapid regeneration may be explained by the potential presence of at least one stem cell type within the tissue or by the existence of growth factors, such as basic fibroblast growth factor, in saliva [Grimm et al, 2014]. Previous research suggested that PAT provided an accessible source of MSCs, which could be used for tissue engineering and tissue regeneration of extraoral tissues in periodontal disease [Roman et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its capability for rapid regeneration may be explained by the potential presence of at least one stem cell type within the tissue or by the existence of growth factors, such as basic fibroblast growth factor, in saliva [Grimm et al, 2014]. Previous research suggested that PAT provided an accessible source of MSCs, which could be used for tissue engineering and tissue regeneration of extraoral tissues in periodontal disease [Roman et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…To date, stem cells have been isolated from a variety of oral tissues, including gingiva [Zhang et al, 2009], periodontal ligament (PDL) [Seo et al, 2004;Hakki et al, 2014], and palatal connective tissue [Roman et al, 2013;Grimm et al, 2014]. They have also been isolated from dental tissues, such as dental papilla [Ikeda et al, 2006], dental follicles [Morsczeck et al, 2005], dental pulp from natal teeth [Karaöz et al, 2010], deciduous teeth [Gronthos et al, 2000;Miura et al, 2003], and adult teeth [Hakki et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако объем донорской кости в полости рта ограничен, взятие аутотрансплантата внеротовым способом сопряжено с дополнительной операционной травмой и привлечением специалистов из смежных об-ластей медицины [8,9]. К недостаткам аллогенных и синтетических остеопластических материалов относят-ся иммунный ответ, инфицирование, низкие прочност-ные характеристики, длительный срок резорбции и не-достаточная первичная стабильность дентальных им-плантатов, устанавливаемых в области синус-лифтинга [10,14].…”
Section: стоматология 1 2016unclassified
“…Особенностью коллагена считается его способность образовывать комплексы с лекарствен-ными и биологически активными веществами, что дает возможность создания лекарственных препа-ратов пролонгированного действия, в которых кол-лаген играет роль депо. Перспективным также явля-ется использование коллагеновой губки в качестве матрицы-носителя для различных тканеинженерных конструкций [9, 10, 12]. Важной задачей является контроль эффективности использования подобных средств на клеточном уровне.…”
unclassified